(untitled) (Medical Forum Monthly, 2024)
Objective: Assessment of the patient’s satisfaction undergoing treatment for haemorrhoids, after stapled haemorrhoidectomy and haemorrhoidal artery ligation methods of surgery at Khawaja Muhammad Safdar Medical College, Sialkot, Pakistan. Study Design: Prospective and analytic study. Place and Duration of study: This study was conducted at the Department of Surgery, Khawaja Muhammad Safdar Medical College, Sialkot from from December 2012 to June 2015. Materials and Methods: All patients presenting in surgical out patients department above 18 years with third degree haemorrhoids were included in the study. Data of 82 patients (stapled haemorrhoidectomy n=55 and haemorrhoidal artery ligation n=27) was collected from December 2012 to November 2015. Patients were distributed in two groups depending upon the surgical procedures carried out. Full detailed history, examination, and investigations were performed. Patients with grade III hemorrhoids underwent the RAR procedure (Recto Anal Repair) i.e. Doppler guided haemorrhoidal artery ligation (DG-HAL) combined with restoration of prolapsed hemorrhoids to their anatomical position with longitudinal sutures. Results of treatment were assessed by regular follow up. Recording of variables and feedbackof the patients with minimum 3 months follow up, was made and analysed. Results: Out of 82 patients included in our study, Male patients were more in number in our study while 43 years came out to be, of the mean age. Something coming out from the anal canal, painful evacuation of bowels, bleeding per rectum and constipation are the chief presenting complaints. Conclusion: Generally, patients with piles except having severe prolapsed haemorrhoids had postoperative pain, lesser complications and acceptable results in long term can be achieved, in patients undergoing Doppler Guided Haemorrhoid Artery Ligation and Recto Anal Repair. Haemorrhoid artery ligation is a procedure associated with much less pain, in comparison to the stapled haemorrhoidectomy and patients can resume normal routine job, early. Long-term complications still require to be seen and assessed by studies with longer follow up. A lot depends on treating surgeon, his experience, skill and acumen.